Does physiotherapy prehabilitation improve pre-surgical outcomes and influence patient expectations prior to knee and hip joint arthroplasty?. (August 2018) - Clode, Nicholas J.; Perry, Meredith A.; Wulff, Lauren
Abstract: Introduction: Evidence supporting physiotherapy prior to hip or knee replacement for decreasing pain and improving function pre and post-operatively is equivocal. This observational cohort study used a mixed-methods approach to investigate whether 8 weeks of physiotherapy led exercise and education ('prehabilitation') would change pain and functional outcomes prior to surgery, and if patients' expectations and satisfaction post-surgery were influenced. Methods: Participants awaiting THR or TKR were recruited (n = 75). Fifty two opted into the 'prehabilitation' group while twenty three opted for usual care. The prehabilitation group included a 45 min exercise and 15 min education session twice weekly for 8 weeks. All participants completed the WOMAC, NRS, Health Thermometer, 5xSTS and TUG outcome measures. Data were collected before and after prehabilitation and 6 weeks after surgery. Qualitative data were collected from 22 participants via telephone interviews and analysed inductively. Results: Both groups improved post surgery. The prehabilitation group showed statistically significant improvements in all outcome measures after prehabilitation (pre-surgery). Participants' felt prehabilitation prepared them well for surgery and influenced expectations post-operatively. Group education talks and the experience of friends and family appeared highly valued information sources. Conclusion: Prehabilitation improved patients' pain and function before hip or knee replacement surgery.